2022
DOI: 10.2196/35554
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Digital Interventions for Preventing Alcohol Consumption in Pregnancy: Systematic Review and Meta-analysis

Abstract: Background Alcohol consumption in pregnancy has been associated with serious fetal health risks and maternal complications. While previous systematic reviews of digital interventions during pregnancy have targeted smoking cessation and flu vaccine uptake, few studies have sought to evaluate their effectiveness in preventing alcohol consumption during pregnancy. Objective This systematic review aims to assess (1) whether digital interventions are effecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 43 publications
(81 reference statements)
0
15
0
2
Order By: Relevance
“… 33 42 A recent meta-analysis of six of the 10 studies included in this review supports the potential of digital interventions. 45 …”
Section: Discussionmentioning
confidence: 99%
“… 33 42 A recent meta-analysis of six of the 10 studies included in this review supports the potential of digital interventions. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Studies examining digital technology and AI in providing preconception and perinatal care for parents and parents‐to‐be, to date, have not included the use of chatbots 22–29 . Because chatbots can help to improve preconception and perinatal health outcomes, 30,31 the insights of parents and parents‐to‐be in using these chatbots deserve further analysis.…”
Section: Introductionmentioning
confidence: 99%
“…18,21 Studies examining digital technology and AI in providing preconception and perinatal care for parents and parents-tobe, to date, have not included the use of chatbots. [22][23][24][25][26][27][28][29] Because chatbots can help to improve preconception and perinatal health outcomes, 30,31 the insights of parents and parents-to-be in using these chatbots deserve further analysis. Therefore, this mixed studies review aims to address this research gap by consolidating findings from both quantitative and qualitative studies to provide a comprehensive understanding of the insights of parents and parents-to-be into using chatbots for their preconception, pregnancy, and postpartum health.…”
Section: Introductionmentioning
confidence: 99%
“…Although the results suggested that both mothers and fathers benefited from the mobile interventions, the lack of data prevented the ability to draw conclusions regarding the relative mobile app effectiveness, and the authors suggested that future studies including fathers are needed [40]. In contrast to the growing popularity and promising findings of digital programs for mothers in the perinatal period [41][42][43][44][45], the authors of this review are not aware of any other reviews that have examined digital interventions (including any digital modalities) for fathers of young children.…”
Section: Introductionmentioning
confidence: 99%